AKTIVITAS ANTIOKSIDAN, SIFAT FISIK DAN SIFAT SENSORIS STIK BUAH NAGA MERAH (Hylocereus polyrhizus): Antioxidant Activity, Physical Properties and Sensory Properties of Red Dragon Fruit Sticks (Hylocereus Polyrhizus) - Farid Musyofa; Supriyanto Supriyanto; Muhammad Fuad Fauzul Mu'tamar (Agroindustrial Technology Journal, 2022)
Red dragon fruit ((Hylocereus polyrhizus)) contains carotene and flavonoid compounds which are antioxidants that are good for the body to consume to help neutralize free radicals that attack body cells. One of the problems with dragon fruit is the high stock of dragon fruit during the harvest but consumer demand is relatively fixed so that the price of dragon fruit is decreasing. Dragon fruit can be processed into a variety of delicious foods and has high nutrition. The purpose of this study was to determine antioxidant activity, physical properties and sensoric properties of red dragon fruit. The experimental design used was a factorial completely randomized design. The factor I is the concentration of dragon fruit (0%, 15% and 30%) while factor II is the frying temperature (150oC and 160oC). The results of this study showed that the treatment of dragon fruit variations had a significant effect on antioxidant activity, sensory aroma, color, texture, taste and overall dragon fruit sticks. The best formulation based on sensory tests was obtained at 30% dragon fruit concentration treatment with a frying temperature of 160oC. Its antioxidant content is 0.946%, water content is 3.83%, hardness is 3699.7 kgf and cohesiveness is 0.17910 kgf.